Living Qur’an and Elderly Piety: A Study of Majelis Dzikrul Ghofilin and Sema’an Al-Qur’an Jantiko Matab in Kediri, Indonesia - M. Mu'tashim Billah; Mubaidi Sulaeman; Carimo Mohomed; Syafik Ubaidila (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2024)
This study examines the Living Qur’an phenomenon and its role in shaping religious piety among elderly congregants in two religious groups in Kediri, East Java, Indonesia: Majelis Dzikrul Ghofilin and Sema’an Al-Qur’an Jantiko Matab. The Living Qur’an concept, as manifested in elderly congregations, represents the embodied and contextual practice of Qur’anic teachings in daily life, fundamentally contributing to individual and collective piety. Through fieldwork utilizing a qualitative methodology informed by Talal Asad’s concept of “discursive tradition,” this research employs participatory observation, in-depth interviews, and documentary analysis. The anthropological analysis focuses on identifying patterns in Living Qur’an practices among elderly congregants, with particular attention to symbolic reception and sensory engagement in religious practices. The research reveals distinctive manifestations of the Living Qur’an in each group. Majelis Dzikrul Ghofilin centers its practice on dhikr (divine remembrance), supplications, and contemplative engagement with Qur’anic verses, fostering spiritual connectivity and emotional resilience. In contrast, Sema’an Al-Qur’an Jantiko Matab emphasizes sustained communal Qur’anic recitation from dawn to nightfall, cultivating devotional practice through extended engagement with sacred text. These complementary approaches demonstrate the versatility of Living Qur’an implementations in enhancing elderly congregants’ spiritual well-being. This study contributes to the scholarly discourse on the Living Qur’an among elderly populations, presenting novel insights into Qur’anic reception and pietistic practices. Furthermore, it establishes a theoretical foundation for understanding religion’s role in shaping elderly worldviews while advancing methodological approaches to studying Qur’anic reception in Muslim communities.